Preparation of rooibos extract-chitosan microparticles: Physicochemical characterisation and stability of aspalathin during accelerated storage. (January 2020) - Human, Chantelle; de Beer, Dalene; Aucamp, Marique; Marx, Isa J.; Malherbe, Christiaan J.; Viljoen-Bloom, Marinda; van der Rijst, Marieta; Joubert, Elizabeth
Abstract: Green rooibos extract containing high levels of aspalathin, a dihydrochalcone antioxidant, and the carrier chitosan, both an antioxidant and antimicrobial agent, was used to produce a dual-purpose food ingredient powder by spray-drying for incorporation into processed meat products. Green rooibos extract was shown to inhibit growth of Escherichia coli, Staphylococcus aureus and Listeria monocytogenes, adding to the functionality of such a powder. Three formulations (50, 100 and 150 g chitosan/kg powder) were compared to the pure spray-dried extract and maltodextrin-containing powders (250 and 500 g maltodextrin/kg powder) in terms of physicochemical properties (particle size and morphology, moisture sorption isotherms, compatibility, bulk density and compressibility) and aspalathin stability during accelerated storage. All the formulations produced amorphous, hygroscopic powders with deliquescence at relative humidity (RH) > 65%. The moisture content of the powders was lower than their monolayer moisture content calculated using the BET and GAB models. Isothermal microcalorimetry showed no interaction between extract and carbohydrate polymers. Aspalathin degradation in the powders, subjected to accelerated stability testing (40 °C/75% RH for 96 h), followed fractional conversion kinetics. The presence of chitosan in the powders decreased the stability of aspalathin during storage compared to the pure extract and maltodextrin-containing powders. Highlights: Green rooibos extract inhibited growth of Listeria monocytogenes. Chitosan, an antimicrobial polymer, improved functionality of rooibos extract. Isothermal microcalorimetry showed no interaction between extract and chitosan. Chitosan decreased aspalathin stability during accelerated storage (40 °C/75% RH).